156k views
3 votes
If f(x) = 4x + 3 and g(x) = 3x, evaluate for X = -1/2

2 Answers

5 votes

Answer:

f(-1/2) = 1

g(-1/2) =-3/2

Explanation:

f(x) = 4x+3

Let x = -1/2

f(-1/2) = 4(-1/2) +3

f(-1/2) = -2 +3

f(-1/2) =1

g(-1/2) = 3(-1/2)

= -3/2

User Vernonk
by
5.5k points
4 votes

Answer:


f(-(1)/(2)) = 1


g(-(1)/(2) ) = -(3)/(2)

Explanation:

Given the function
f(x) = 4x + 3 and the function
g(x) = 3x, to evaluate for
x=-(1)/(2), you need to substitute it into each function.

Then, for the function f(x), when
x=-(1)/(2), you get:


f(-(1)/(2)) = 4(-(1)/(2)) + 3


f(-(1)/(2)) = 4(-(1)/(2)) + 3


f(-(1)/(2)) = -(4)/(2)+ 3


f(-(1)/(2)) = -2 + 3


f(-(1)/(2)) = 1

For the function g(x), when
x=-(1)/(2), you get:


g(-(1)/(2) ) = 3(-(1)/(2))


g(-(1)/(2) ) = -(3)/(2)

User Talg
by
5.1k points